Indigenous health worker support for patients with poorly controlled type 2 diabetes: study protocol for a cluster randomised controlled trial of the Mana Tū programme. Issue 12 (14th December 2018) - Selak, Vanessa; Stewart, Tereki; Jiang, Yannan; Reid, Jennifer; Tane, Taria; Carswell, Peter; Harwood, Matire
Abstract : Introduction: Type 2 diabetes mellitus (T2DM) and its complications are more common among Māori and Pacific people compared with other ethnic groups in New Zealand. Comprehensive and sustained approaches that address social determinants of health are required to address this condition, including culturally specific interventions. Currently, New Zealand has no comprehensive T2DM management programme for Māori or Pacific people. Methods and analysis: The Mana Tū programme was developed by a Māori-led collaborative of primary healthcare workers and researchers, and codesigned with whānau (patients and their families) in order to address this gap. The programme is based in primary care and has three major components: a Network hub, Kai Manaaki (skilled case managers who work with whānau with poorly controlled diabetes) and a cross-sector network of services to whom whānau can be referred to address the wider determinants of health. The Network hub supports the delivery of the intervention through training of Kai Manaaki, referrals management, cross-sector network development and quality improvement of the programme. A two-arm cluster randomised controlled trial will be conducted to evaluate the effectiveness of the Mana Tū programme among Māori, Pacific people or those living in areas of high socioeconomic deprivation who also have poorly controlled diabetes (glycated haemoglobin, HbA1c, >65 mmol/mol (8%)), compared with being on a wait list for the programme. A total of 400 participants will be included from 10 general practices (5 practices per group, 40 participants per practice). The primary outcome is HbA1c at 12 months. Secondary outcomes include blood pressure, lipid levels, body mass index and smoking status at 12 months. This protocol outlines the proposed study design and analysis methods. Ethics and dissemination: Ethical approval for the trial has been obtained from the New Zealand Health and Disability Ethics Committee (17/NTB/249). Findings will be presented to practices and their patients at appropriate fora, and disseminated widely through peer-reviewed publications and conference presentations. Trial registration number: ACTRN12617001276347; Pre-result.